Antibacterial Ti–Cu implants: A critical review on mechanisms of action - Pezhman Mahmoudi; Mohammad Reza Akbarpour; Hengame Babaei Lakeh; Fengjuan Jing; Mohammad Reza Hadidi; Behnam Akhavan (Materials Today Bio, 2022)
Titanium (Ti) has been widely used for manufacturing of bone implants because of its mechanical properties, biological compatibility, and favorable corrosion resistance in biological environments. However, Ti implants are prone to infection (peri-implantitis) by bacteria which in extreme cases necessitate painful and costly revision surgeries. An emerging, viable solution for this problem is to use copper (Cu) as an antibacterial agent in the alloying system of Ti. The addition of copper provides excellent antibacterial activities, but the underpinning mechanisms are still obscure. This review sheds light on such mechanisms and reviews how incorporation of Cu can render Ti–Cu implants with antibacterial activity. The review first discusses the fundamentals of interactions between bacteria and implanted surfaces followed by an overview of the most common engineering strategies utilized to endow an implant with antibacterial activity. The underlying mechanisms for antibacterial activity of Ti–Cu implants are then discussed in detail. Special attention is paid to contact killing mechanisms because the misinterpretation of this mechanism is the root of discrepancies in the literature.